2010
DOI: 10.1136/jme.2010.039172
|View full text |Cite
|
Sign up to set email alerts
|

Choice is not the issue. The misrepresentation of healthcare in bioethical discourse

Abstract: The principle of respect for autonomy has shaped much of the bioethics' discourse over the last 50 years, and is now most commonly used in the meaning of respecting autonomous choice. This is probably related to the influential concept of informed consent, which originated in research ethics and was soon also applied to the field of clinical medicine. But while available choices in medical research are well defined, this is rarely the case in healthcare. Consideration of ordinary medical practice reveals that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 27 publications
(21 reference statements)
0
18
0
Order By: Relevance
“…26 However, it has also been observed that too many options can leave consumers feeling anxious and overwhelmed, 27 with patients at particular risk owing to the nature of clinical decision-making: as a health-care consumer, the patient is, by definition, sick, dependent on the professional for treatment and often lacking the knowledge to make an independent decision and the time to deliberate. 28 Moreover, it is well documented that not all patients want to choose their treatment; 29,30 and, as Pilnick and Dingwall 31 highlight, reviews of the literature on patient centeredness show mixed results with respect to positive health outcomes (although they suggest increased rates of patient satisfaction). We did not start, then, from the assumption that choice ought to be more widely offered to patients.…”
Section: Models Versus Practices: Our Methodological Starting Pointmentioning
confidence: 99%
See 3 more Smart Citations
“…26 However, it has also been observed that too many options can leave consumers feeling anxious and overwhelmed, 27 with patients at particular risk owing to the nature of clinical decision-making: as a health-care consumer, the patient is, by definition, sick, dependent on the professional for treatment and often lacking the knowledge to make an independent decision and the time to deliberate. 28 Moreover, it is well documented that not all patients want to choose their treatment; 29,30 and, as Pilnick and Dingwall 31 highlight, reviews of the literature on patient centeredness show mixed results with respect to positive health outcomes (although they suggest increased rates of patient satisfaction). We did not start, then, from the assumption that choice ought to be more widely offered to patients.…”
Section: Models Versus Practices: Our Methodological Starting Pointmentioning
confidence: 99%
“…Where no treatment choice is constructed for the patient, this is premised on -and justified with respect to -the diagnostic decisions made by the neurologist. As Agledahl et al 28 argue, to avoid making such decisions would often be unethical (e.g. if an available option has no medical justification for a particular patient) or impractical (e.g.…”
Section: When Participants Agree That Choice Is Absentmentioning
confidence: 99%
See 2 more Smart Citations
“…'Choices' are framed by professional knowledge and the availability of restricted options. 48,187 Some people are unaccustomed to making plans, and not disposed to choose, especially when faced with decisions about matters of great significance of which they have no prior knowledge or experience. Indeed, the obligation to choose may be experienced as burdensome.…”
Section: Helping Patients To Prepare For Deathmentioning
confidence: 99%